Implementación del sistema de gestión de seguridad y salud en el trabajo bajo los lineamientos de los decretos 1072 de 2015, 052 de 2017 y la resolución 1111 de 2017 para la empresa Bricocinas (2018)
The present degree work includes the methodology and results achieved in the implementation of a Management and Health and Safety System at work, under the parameters of Decrees 1072 of 2015, 052 of 2017 and Resolution 1111 of 2017 at the company Bricocinas, located in the city of Villavicencio whose productive main activity is the manufacture of integral kitchens.